Improvement of Lumbar Bone Mass after Infliximab Therapy in Crohn’s Disease Patients - Marina Mauro; Vladimir Radovic; David Armstrong (Canadian Journal of Gastroenterology)
BACKGROUND: Patients with Crohn’s disease (CD) have a high risk of developing osteoporosis, but the mechanisms underlying bone mass loss are unclear. Elevated proinflammatory cytokines, such as tumour necrosis factor-alpha (TNFα), have been implicated in the pathogenesis of bone resorption.